Highly Effective Markerless Genetic Manipulation of Streptococcus suis Using a Mutated PheS-Based Counterselectable Marker - Gao, Guangjuan; Wei, Dong; Li, Gang; Chen, Ping; Wu, Liujun; Liu, Siguo; Zhang, Yueling (Frontiers in Microbiology, 2022)
Despite the importance of zoonotic pathogen Streptococcus suis, an efficient markerless genetic manipulation system is still lacked for further physiological and pathological studies on this bacterium. Several techniques have been developed for markerless genetic manipulation of S. suis utilizing either a temperature-sensitive vector or a counsterselectable markers (CSM), however, at present the efficiency of these techniques are not very satisfactory. In this study we developed a strategy for markerless genetic manipulation of S. suis employing a CSM based on a conditionally lethal mutant allele of pheS, which encodes the α-subunit of phenylalanyl-tRNA synthetase (PheS). This mutant pheS, mPheS, was constructed by introducing site-directed mutations for a T261S/A315G double-substitution and a number of silent mutations to decrease its similarity with the endogenous wild type pheS gene (wtPheS). Additionally, five potentially strong promoters from S. suis were screened for their ability to drive high level expression of mPheS, thus to endow the carrier strain with sufficient sensitivity to the phenylalanine analog p-chloro-phenylalanine (p-Cl-phe). Insertion of these P-mPheS cassettes into a vector or into the chromosomal locus via a linked erythromycin resistance gene revealed that mPheS allele driven by promoters P0530 and P1503 renders S. suis sensitive to as low as 0.01% (or 0.5 mM) of p-Cl-phe. This offers two potential CSMs for S. suis with p-Cl-phe as a counterselective agent. P1503-mPheS was revealed to be 100% efficient for counter-selection in S. suis by application in a precise gene-deletion. Using P1503-mPheS as a CSM, a two-step insertion and excision strategy for markerless genetic manipulation of S. suis was developed, supplying a powerful tool for markerless genetic manipulation of S. suis.